TINJAUAN QANUN ACEH NOMOR 5 TAHUN 2016 TENTANG PENCABUTAN QANUN NOMOR 9 TAHUN 2014 TENTANG PEMBENTUKAN BANK ACEH SYARI’AH - Mukhlisuddin, Teuku (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2022)
The existence of Qanun Number 5 of 2016 concerning the Revocation of Qanun Number 9 of 2014 concerning the Establishment of the Aceh Sharia Bank has caused disputes among Acehnese elite figures. For the government, the revocation of Qanun Number 9 of 2014 is a step to speed up conversion. Meanwhile, according to M. Jafar, the implementation of the conversion of Bank Aceh from the conventional system to sharia does not require Qanun, except for the formation of a new bank or spin off (separation). In fact, the Financial Services Authority (OJK) instructed the Aceh government to revoke Qanun Number 9 of 2014 to speed up conversion permits from the Financial Services Authority. So that the authors are interested in exploring deeper information about the reasons for the Aceh government to revoke Qanun Number 9 of 2014 concerning the establishment of Bank Aceh Syariah in the form of a spin off. This type of research is a library research using a normative juridical approach, namely Qanun Number 5 of 2016 concerning the revocation of Qanun Number 9 of 2014 concerning the Establishment of the Aceh Sharia Bank. From this research, it can be seen that the Aceh Qanun which was issued in 2014 and then revoked by the Aceh government in 2016 is not a requirement to obtain a license to convert Conventional Aceh Bank into sharia.